Prediction of giant magnetoelectric effect in LaMnO3/BaTiO3/SrMnO3 superlattice: The role of n-type SrMnO3/LaMnO3 interface - Chen, L. Y. (2014)
We study the magnetoelectric coupling for the [001]-oriented (LaMnO3)2/(BaTiO3)5/(SrMnO3)2 superlattice, by means of the density functional theory. An interesting transition between ferromagnetic ordering and antiferromagnetic ordering is demonstrated by switching ferroelectric polarization in short-period superlattice structure. The predicted ferroelectrically induced magnetic reconstruction is less sensitive to the choice of Coulomb-correction U within GGA + U scheme. A possible explanation is given in terms of the favorable effect of n-type SrMnO3/LaMnO3 interface. Our results suggest that a sizable magnetoelectric effect may be achieved in the short-period LaMnO3/BaTiO3/SrMnO3 superlattice, hence promising application in electrically controlled magnetic data storage.